A research on the Quranic foundations of social etiquette emphasizing the views of Ayatollah Javadi Amoli - ali modaber (اخلاق وحیانی)
The field of human communication with other human beings and his social life style are an important part of the teachings and rulings of the Holy Quran. The Qur'an has expressed both the outlines of many social doctrines in the form of "do's and don'ts" and some foundations and infrastructures of these teachings in the form of "beings and non-beings". There are many researches and writings about social teachings; However, the study of the foundations of social behavior has not received the attention of Quranic scholars, and this justifies the necessity of this research, therefore, the main problem of this research is to find the Quranic foundations of social etiquette, and its findings are as follows: some The Quranic principles of social etiquette are the basis of general social teachings, and some others are the basis of the teachings of believers in particular. The first category consists of: 1. Human dignity; 2. Conjunction of right and duty in social relations; 3. Balance of rights and duties; 4. Precedence of social interests over individual interests, and the second category is as follows: 1. Sanctity of faith; 2. Religious brotherhood; 3. Faithful guardianship of believers over each other. This article, in brief, also examines the effect of the mentioned foundations on social teachings. The research method in this article is descriptive-revelation and its information processing method (data processing) is explanatory and analytical, and its information gathering method is library.